The timing of employment breaks: how does it affect pension benefits? Empirical evidence from Germany - Niklas Potrafke (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper provides empirical evidence how the timing of employment breaks affects pension benefits in Germany. Analysing the biographical data set from the German Pension Insurance (SUF VVL 2004) the employment histories of individuals aged 21 to 60 can be mirrored in detail. We relate differences in pension benefits to employment breaks due to unemployment and parental leave in the individual life cycle, distinguishing by gender. Three different career phases (early, middle and late) are distinguished and respective social policy phases are considered. As predicted by human capital theory, the losses due to career interruptions in the early and middle employment period differ. However, the negative effects due to unemployment in the late employment period are only weak. This finding detects special characteristics of the covered age-groups in the data set.
Keywords: J26; J24; 330; employment histories; career interruptions; pension benefits; Gesetzliche Rentenversicherung; Erwerbsverlauf; Lebenszyklus; Deutschland